Ascorbate deficiency results in decreased collagen production: Under-hydroxylation of proline leads to increased intracellular degradation - Berg, Richard A.; Steinmann, Beat; Rennard, Stephen I.; Crystal, Ronald G. (Archives of biochemistry and biophysics, 1983)
Collagen production by cultured human lung fibroblasts was examined when the cells were made deficient in ascorbate. Cells grown in the absence of ascorbate produced 30% less collagen during a 6-h labeling period than cells incubated with as little as 1 μg/ml ascorbate during the labeling period. Cells grown without ascorbate produced under-hydroxylated collagen which was subject to increased intracellular degradation from a basal level of 16% to an enhanced level of 49% of all newly synthesized collagen. The likely mechanism for increased intracellular degradation is the inability of under-hydroxylated collagen to assume a triple-helical conformation causing it to be susceptible to intracellular degradation. Measurement of collagen production by enzyme linked immunoassay (ELISA) using antibodies directed against triple-helical determinants of collagen showed that both types I and III collagens were affected. In contrast, another connective tissue component, fibronectin, was not affected. Analysis by ELISA showed a greater decrease in collagen production than did analysis by the collagenase method, suggesting that some non-helical collagen chains (detected by collagenase but not by ELISA) were secreted in the absence of ascorbate. These results provide a mechanism to account, in part, for the deficiency of collagen in connective tissues which occurs in a state of ascorbate deficiency.